2009
DOI: 10.1177/112070000901900111
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the NICE Guidelines for Venous Thromboprophylaxis; A National Survey of Hip Surgeons

Abstract: The 2007 United Kingdom National Institute for Health and Clinical Excellence (NICE) thromboprophylaxis guidelines concerning hip arthroplasty remain contentious in spite of significant evidence. A survey among British Hip Society members was performed to investigate the impact of these guidelines. Information on thromboprophylactic measures before and after guideline publication was gathered for three categories; Total Hip Replacement (THR), hip fracture and high-risk patients (as defined by NICE). The respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Expert investigators and societies [including the American College of Chest Physicians (ACCP)] in the field of thromboprophylaxis were also contacted to inquire about available questionnaires evaluating the knowledge of physicians about VTE prophylaxis. Ultimately, a few valuable questionnaires were located [11][12][13][14][15][16][17][18]. However, contrary to topics such as cardiopulmonary resuscitation for which validated questionnaires exist to evaluate the physicians' knowledge of the guideline recommendations [19], it became evident that none of the located questionnaires [11][12][13][14][15][16][17][18] were developed in a systematic way to comprise the majority of issues about VTE prophylaxis, even for a specialty setting.…”
Section: Questionnaire Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Expert investigators and societies [including the American College of Chest Physicians (ACCP)] in the field of thromboprophylaxis were also contacted to inquire about available questionnaires evaluating the knowledge of physicians about VTE prophylaxis. Ultimately, a few valuable questionnaires were located [11][12][13][14][15][16][17][18]. However, contrary to topics such as cardiopulmonary resuscitation for which validated questionnaires exist to evaluate the physicians' knowledge of the guideline recommendations [19], it became evident that none of the located questionnaires [11][12][13][14][15][16][17][18] were developed in a systematic way to comprise the majority of issues about VTE prophylaxis, even for a specialty setting.…”
Section: Questionnaire Preparationmentioning
confidence: 99%
“…A few questionnaires do exist that address the knowledge of physicians about various thromboprophylaxis issues [11][12][13][14][15][16][17][18]. Interestingly, some of such questionnaires used 'case vignettes' as their main body of questions in order to evaluate the physicians' knowledge in a setting similar to their real-world everyday practice [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…180 Nevertheless, in 2011 Duff et al reported that the following factors were identified as barriers to thromboprophylaxis guideline uptake in a metropolitan Sydney hospital: A lack of motivation to change, a lack of systems support, a knowledge or awareness deficit and disputed evidence.…”
mentioning
confidence: 99%
“…A retrospective study by Yu et al [8] found that the overall compliance with (ACCP) guidelines for the prevention of VTE in six American hospitals was only 13.3%, ranging from 2.8% for neurosurgery to 52.4% for orthopaedic surgery. A survey amongst surgeons in the United Kingdom by Sharif et al [9] showed that only 7% of respondents were adhering to NICE guidance after hip fracture surgery and 44% after hip arthroplasty.…”
mentioning
confidence: 99%